Dynamics of immune response to exogenous Staphylococcus aureus endophthalmitis with using antibacterial photodynamic therapy with methelene blue and intravitreal antibiotic in a rabbit model (Ukrainian Journal of Ophthalmology, 2026)
Introduction. It is necessary to study the influence of antibacterial photodynamic therapy (APDT) with 0.1 % methylene blue (MB) alone and in combination with intravitreal injection (IVI) of the antibiotic on the immune response to exogenous Staphylococcus aureus endophthalmitis.Purpose: to make a comparative analysis of the dynamics of local and general immune response to exogenous Staphylococcus aureus endophthalmitis with using APDT with 0.1 % MB and IVI of 1.0 mg Vancomycin independently, as well as using these techniques in the complex.Material and methods. In the experimental study four groups of rabbits are presented: I — without using any treatment, II — APDT with 0.1 % MB, III — IVI of 1.0 mg Vancomycin, IV — APDT with 0.1 % MB and IVI of 1.0 mg Vancomycin. Results: In the groups II and III dynamics of immune response did not differ, the normalization of the indices of immunity occurred at 21—30 days of the experiment, when the IV group of animals from the 10-day study.Conclusions. Using of APDT with 0.1 % MB and IVI of 1.0 mg Vancomycin together led to normalization of immune status of rabbit and elimination from the inflammatory process autoimmune component from day 10. At the same time, using these methods separatly led to the same result, but only from the day 21.
Keywords: Staphylococcus aureus endophthalmitis; immune response; experiment; antibacterial photo-dynamic therapy; methylene blue; Vancomycin